Comparison TTW Model with POE in Creative and Critical Thinking Skills in Physics lesson: Meta-Analysis Study - Aziz Kurniawan (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
The research conducted by the researcher is a Meta-Analysis study from the results of research that has been carried out by previous researchers to compare the TTW model with the POE model on creative thinking skills and critical thinking in Physics lessons. Researchers studied several journals related to the problems faced, namely as many as 30 National articles indexed by Google Scholar. articles that are the research objectives with the theme of creative thinking models and critical thinking models TTW or POE. Based on this, there are 3 variables, namely (1) the TTW model, (2) the POE model, and (3) the ability to think creatively and critically. From the data analysis using the ANCOVA technique that has been carried out, both models provide an effect size with a large criterion of 0.652. While the influence of the two models can be said to be almost the same, namely the TTW model of 76.58 and the POE model of 74.00 so it can be concluded that the TTW and POE models have a major effect on creative and critical thinking skills. thinking in Physics lessons.